Coordinated demethylation of H3K9 and H3K27 is required for rapid inflammatory responses of endothelial cells. (3rd March 2020) - Higashijima, Yoshiki; Matsui, Yusuke; Shimamura, Teppei; Nakaki, Ryo; Nagai, Nao; Tsutsumi, Shuichi; Abe, Yohei; Link, Verena M; Osaka, Mizuko; Yoshida, Masayuki; Watanabe, Ryo; Tanaka, Toshihiro; et al.
Abstract: Histone H3 lysine‐9 di‐methylation (H3K9me2) and lysine‐27 tri‐methylation (H3K27me3) are linked to repression of gene expression, but the functions of repressive histone methylation dynamics during inflammatory responses remain enigmatic. Here, we report that lysine demethylases 7A (KDM7A) and 6A (UTX) play crucial roles in tumor necrosis factor (TNF)‐α signaling in endothelial cells (ECs), where they are regulated by a novel TNF‐α‐responsive microRNA, miR‐3679‐5p. TNF‐α rapidly induces co‐occupancy of KDM7A and UTX at nuclear factor kappa‐B (NF‐κB)‐associated elements in human ECs. KDM7A and UTX demethylate H3K9me2 and H3K27me3, respectively, and are both required for activation of NF‐κB‐dependent inflammatory genes. Chromosome conformation capture‐based methods furthermore uncover increased interactions between TNF‐α‐induced super enhancers at NF‐κB‐relevant loci, coinciding with KDM7A and UTX recruitments. Simultaneous pharmacological inhibition of KDM7A and UTX significantly reduces leukocyte adhesion in mice, establishing the biological and potential translational relevance of this mechanism. Collectively, these findings suggest that rapid erasure of repressive histone marks by KDM7A and UTX is essential for NF‐κB‐dependent regulation of genes that control inflammatory responses of ECs. Synopsis: Comprehensive analysis of epigenetic responses during early inflammation in endothelial cells reveals that lysine demethylase 7A and 6A act cooperatively to rapidly erase repressive histone marks, which is required for activation of the pro‐inflammatory TNF‐α/NF‐κB‐signaling pathway. Lysine demethylase 7A (KDM7A) and 6A (UTX) cooperatively control NF‐κB‐dependent transcription in mammalian vascular endothelial cells. Demethylation of repressive histone marks by KDM7A and UTX is critical for early inflammatory responses. KDM7A and UTX are associated with TNF‐α‐induced chromatin looping of super enhancers. Pharmacological inhibition of KDM7A and UTX reduces leucocyte adhesive interactions with endothelial cells in mice. Abstract : Comprehensive analysis of epigenetic responses suggests that rapid erasure of repressive histone marks by KDM7A and UTX is essential for NF‐κB‐dependent inflammatory gene regulation.